Herpes simplex virus 1 interferes with autophagy of murine dendritic cells and impairs their ability to stimulate CD8+ T lymphocytes. Issue 10 (31st August 2017) - Budida, Ramachandramouli; Stankov, Metodi V.; Döhner, Katinka; Buch, Anna; Panayotova‐Dimitrova, Diana; Tappe, Kim A.; Pohlmann, Anja; Sodeik, Beate; Behrens, Georg M. N.
Abstract: The MHC class I presentation is responsible for the presentation of viral proteins to CD8 + T lymphocytes and mainly depends on the classical antigen processing pathway. Recently, a second pathway involving autophagy has been implicated in this process. Here, we show an increase in the capacity of murine dendritic cells (DCs) to present viral antigens on MHC class I after infection with a mutant herpes simplex virus 1 (HSV‐1‐Δ34.5), lacking infected cell protein 34.5 (ICP34.5), when compared to its parental HSV‐1 strain. The ICP34.5 protein counteracts host cell translational arrest and suppresses macroautophagy, and the lack of this protein resulted in a low viral protein abundance, which was processed and presented in an efficient way. Our study demonstrates an important role of autophagy in processing endogenous viral proteins in HSV‐1‐infected DCs. Abstract : ICP34.5 protein of HSV‐1 helps the virus to counteract host cell responses such as translational shutoff and autophagic degradation ( left ). Deletion of ICP34.5 restores efficient MHC class I presentation via autophagy despite reduced abundance of viral antigens ( right ).